A multi-attribute examination of consumer conformity in group-level ordering. Issue 1 (February 2018) - Lee, Jacob C.; Kim, Jungkeun; Kwak, Kyuseop
Highlights: This paper has examined consumers' individual choices in group settings. This paper finds the group conformity and group referencing effects. The item ordered later is similar to the previously ordered item(s) in group settings. Group referencing effect has been founded in the various attributes level. Abstract: Using real data acquired from transaction receipts at a cafe, the present research examined individuals' menu choices made in a group setting. Building on previous research, the present research proposed and examined what we call the group referencing effect, and found that individuals' menu choices were more likely to conform to the precedent menu choices made by the others in their group. A unique empirical contribution of the present research is that conformity was assessed and emerged at two levels: end-choice level (whether the choices are the same) and attribute-level (whether the attribute(s) of the choices are the same, independent of whether the end-choice is the same; i.e., similarity). Theoretical and practical implications are discussed. Chinese Abstract: 本研究通过在咖啡馆交易收据中获得的真实数据, 探讨了个人在群体环境中进行的菜单选择. 在之前研究的基础上, 本研究提出并探讨了我们所谓的群体参照效应, 并发现个人的菜单选择更有可能跟从所属群组中其他人先行做出的菜单选择. 本次研究的一项独特的实证性贡献是, 从众性的评估和出现分两个层面:最终选择层面 (选择是否相同)和属性层面 (选择的属性是否相同, 这独立于最终选择是否相同, 即相似性). 理论和实践影响均得到探讨.